Continuous or interrupted chest compressions for EMS-performed cardiopulmonary resuscitation - Inaba, Hideo; Maeda, Testuo (Journal of Thoracic Disease; Vol 8, No 1 (January 30, 2016): Journal of Thoracic Disease, 2016)
High-quality cardiopulmonary resuscitation (CPR), which can supply blood to critical organs such as the heart, lungs, and brain, with an optimal level of perfusion pressure, is known to be essential for the return of spontaneous circulation (ROSC) and a good outcome in case of out-of-hospital arrests (OHCAs) (1,2). The CPR guidelines 2000 (3) recommended the use of ventilation for OHCA victims with a small tidal volume and low inspiratory pressure to avoid gastric inflation. These guidelines also recommended chest compression (CC) at a rate of 100 compressions per minute with a complete release of pressure after each CC to achieve optimal forward blood flow.